Schedule-dependency of doxorubicin and vinblastine in EAT tumours in mice - Auersperg, Marija (Radiology and oncology (Ljubljana), 2006)
Background. Antitumour schedule-dependency of the doxorubicin and vinblastine combination was explored. Materials and methods. Intraperitoneal Ehrlich ascites tumours (EAT) syngeneic to CBA mice were treated with vinblastine ar doxorubicin alone, or in combined treatment schedules. Results. Combinations of doxorubicin and vinblasfine administered at 48-h, but not at 24-h interval,regardless of the sequence of drugs, significantly reduced the numberof tumour cells in the ascites in corrtparison with all other treatments. In the combined treatment schedules, the predominant morphologicalchanges as well as DNA distribution pattern were dependent on thefirst drug applied. Regardless of the sequence of the drugs, median survival times of animals did not significantly differ between the treatment groups. Conclusions. The effect of combination of vinblastine and doxorubicin is schedule-dependent. The time interval, but not the sequence of drugs seems to be crucial for the observed effect. The data from preclinical studies are important for planning combined treatment schedules in clinical setting.
Keywords: poskusi; rak (medicina); therapy; zdravljenje